Application Of Multi-Criteria Decision Making Approaches In Prioritizing Highway Bridges Inventory For Seismic Retrofitting - Yousefi, Ali (2013)
Many of the bridges are old or were designed without seismic design considerations in areas with potential earthquake hazard. These bridges are vulnerable from even moderate earthquakes and require to be retrofitted in some degree for reducing the future social and economic costs. Besides, the process of seismic retrofitting is extremely costly and time consuming moreover the constraint in resources prevents the retrofitting of all the existing bridges simultaneously. Hence, the bridges must be prioritized with simultaneous consideration of multiple criteria including technical and socioeconomic issues. This study intends to identify the major criteria and their weight for evaluation of highway bridges and providing an effective technique to prioritize the bridges. Suggested criteria include structural vulnerability, seismic hazard, anticipated service life, average daily traffic, interface with other lifelines, alternative routes and bridge importance. To assess the weight of criteria the Analytic Hierarchy Process (AHP) technique is carried out. Since the problem involving a large number of alternatives (bridges) and multiple criteria, VIKOR (VlseKriterijumskaOptimizacija I KompromisnoResenje) and TOPSIS (Technique for Order Preference by Similarity to an Ideal Solution) methods as Multi-Criteria Decision-Making (MCDM) model are applied for prioritizing of bridges. These methods reduce multitude alternative performances into a single value and prioritize the alternatives (bridges) based on their ranking score.